A study on the laws governing child care centres in Malaysia / Amelia Masran, Nur Syarah Shaffiee and Nurul Wahida Amalin Abdul Aziz - Masran, Amelia; Shaffiee, Nur Syarah; Abdul Aziz, Nurul Wahida Amalin (2014)
Child care centre is a place whereby parents send their children to be looked after for a few hours during the day with agreed payment. However, the numbers of child abuse and death reports at child care centres are increasing over the years. Even though there are laws that govern this matter, the effectiveness is questioned. Therefore, this study aims to analyse the laws that govern the child care centre in Malaysia. In this research, we can conclude that the main problems regarding the abuse and death of children at child care centres are due to the illegal child care centres, the lack of implementation of laws governing the child care centre and the unqualified child minders. Interviews with the president of the Association of Registered Childcare Providers Malaysia and a child care operator in Shah Alam were used to collect data about the problems and the reality in operating a child care centre in Malaysia. The preliminary results of the research show that there are complicated procedures in the registration of the child care centre which led to many illegal child care centres. Moreover, lack of enforcement of the laws by relevant authorities contributes to the increase in the number of child abuse and death at the child care centres. Following a critical analysis of the preliminary research results, some recommendations will be presented to improve the system of registration, inspection and qualification of child minders.